1993
DOI: 10.2466/pr0.1993.72.2.667
|View full text |Cite
|
Sign up to set email alerts
|

Personality Subgroups in an Inpatient Vietnam Veteran Treatment Program

Abstract: Millon Clinical Multiaxial Inventory personality profiles of 250 male inpatient Vietnam veterans were examined to locate subgroups within that population. Using a hierarchical cluster analysis to form relatively homogeneous groups, four clusters were identified which accounted for 98% of the population. Three clusters had Millon profiles suggestive of a stress reaction and one cluster had a profile indicative of an antisocial adjustment. As measured by a PTSD subscale of the Minnesota Multiphasic Personality I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Twenty‐three studies reported the types of personality problems experienced by adults who had been exposed to catastrophic trauma using nine different personality measures (Table ). Nine studies that assessed personality traits according to DSM‐III and DSM‐IV criteria (Funari, Piekarski, & Sherwood, ; Hyer, Woods, Boudewyns, Bruno, & O'Leary, ; Hyer, McCraine, Boudewyns, & Sperr, ; Piekarski, Sherwood, & Funari, ; Richman & Frueh, ; Robert et al, ; Shea, Zlotnick, & Weisberg, ; Sherwood, Funari, & Piekarski, ; Taylor, Asmundson, & Carleton, ) found the most frequent to be avoidant (7/9), borderline (6/9), passive–aggressive (6/9) and schizoid traits (5/9). Three studies assessing for DESNOS reported that the most frequent personality difficulties were related to affect and impulse regulation (problems with regulating anger, self‐destructive behaviour, suicidal preoccupation and excessive risk taking), altered systems of meaning (hopelessness and despair) and altered self‐perception (permanent damage, guilt and shame) (Ford, ; Jongedijk, Carlier, Schreuder, & Gersons, ; Morina & Ford, ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐three studies reported the types of personality problems experienced by adults who had been exposed to catastrophic trauma using nine different personality measures (Table ). Nine studies that assessed personality traits according to DSM‐III and DSM‐IV criteria (Funari, Piekarski, & Sherwood, ; Hyer, Woods, Boudewyns, Bruno, & O'Leary, ; Hyer, McCraine, Boudewyns, & Sperr, ; Piekarski, Sherwood, & Funari, ; Richman & Frueh, ; Robert et al, ; Shea, Zlotnick, & Weisberg, ; Sherwood, Funari, & Piekarski, ; Taylor, Asmundson, & Carleton, ) found the most frequent to be avoidant (7/9), borderline (6/9), passive–aggressive (6/9) and schizoid traits (5/9). Three studies assessing for DESNOS reported that the most frequent personality difficulties were related to affect and impulse regulation (problems with regulating anger, self‐destructive behaviour, suicidal preoccupation and excessive risk taking), altered systems of meaning (hopelessness and despair) and altered self‐perception (permanent damage, guilt and shame) (Ford, ; Jongedijk, Carlier, Schreuder, & Gersons, ; Morina & Ford, ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite considerable previous work identifying classes on the basis of personality and broader psychopathology (e.g., Elhai et al, 2003;Forbes et al, 2003;Hyler, Davis, Albrecht, Boudewyns, & Wood, 1994;Piekarski et al, 1993) the absence of a unifying conceptual model, and the fact that earlier studies adopted an exploratory approach, resulted in the failure to identify consistencies across these classes and hence to gain benefit from a growing body of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was possible to draw out common features among the differing subgroups identified in these studies, such as the aggressive stress group of Piekarski et al (1993), the disinhibition/externalizing group (Forbes et al, 2003), and Hyer's antisocial group, a difficulty in integrating the findings of the above research was the absence of a unifying model of personality and psychopathology upon which to conceptualize these subgroups. In this context, Miller, Greif, and Smith (2003) drew on the work of Krueger (1999) and sought to test whether clinically meaningful subtypes differing in propensities towards internalizing versus externalizing comorbidity would be observed within a PTSD sample.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of traumatic stress personality disorder derives from a formulation based on a review of the phenomenological, conceptual, diagnostic, clinical, and empirical literature (Hyer & Boudewyns, 1985;Hyer, Woods. & Boudewyns, 1991;Piekarski, Sherwood, & Funari, 1993;Reich, 1989;Sherwood, Funari, & Piekarski, 1990;WHO, 1992;Wilson & Walker, 1990) and from the author's 20 years of theory-building, supervision, consultation, and direct treatment of hundreds of child and adult victims suffering the ill effects of physical and emotional family and community violence, war, sexual victimization, disasters, and of motor vehicle accidents. The focus is on the interactivity of PTSD and PD, on the presumed functional transactional effects between PTSD and the stable instability of personality structure in traumatized persons.…”
mentioning
confidence: 99%